Cephalopod Experimental Projected Habitat (CEPH): Virtual Reality for Underwater Organisms - Josef, Noam (Frontiers in Marine Science, 2018)
Cephalopods’ visually driven, dynamic and diverse skin display makes them a key animal model in sensory ethology and camouflage research. Development of novel methods is critically important in order to monitor and objectively quantify cephalopod behavior. In this work, the development of Cephalopod Experimental Projected Habitat (CEPH) is described. This newly developed experimental design bridges computational and ethological sciences, providing a visually controlled arena which requires limited physical space and minimal previous technical background. Created from relatively inexpensive and readily available materials, the experimental apparatus utilizes reflected light which closely resembles natural settings. Preliminary results suggest the experimental design reproducibly challenges marine organisms with visually dynamic surroundings, including videos of prey and predator. This new approach should offer new avenues for marine organism sensory research and may serve researchers from various fields.